Operative orthopädische Hämophilie behandlung - Wallny, T. (Hämostaseologie, 2010)
In particular health economists promise to improve healthcare processes, cost-effectiveness and outcomes by standardised procedures. In the area of EOS indication, operative procedures and postal-surgical pain therapy can partly be standardised. In addition, clinical pathways have impact on the organisation of care if the care process is structured in a standardised way. On these four subjects examples are demonstrated. Elective orthopaedic surgery in haemophilia can be standardised. Nevertheless, it may not be forgotten that these patients can be categorised only restrictedly and the individual, interdisciplinary treatment must be prior to clinical standards.
Keywords: Haemophilia; clinical pathways; standardization